DEVELOPMENT OF LEARNING RESOURCES BY DESIGN IN ISLAMIC RELIGIOUS EDUCATION LEARNING FOR HIGH SCHOOL STUDENTS - Arifatul Mufitda; Ahmad Jaeni Dahlan; Edi Nurhidin; Makhfud Makhfud (UIN Antasari Banjarmasin, 2026)
Abstract: This paper aims to examine the development of learning resources by design in Islamic Religious Education (PAI) and Character Building (Budi Pekerti) learning in grade XI high schools (SMA/SMK). The research method used is R&D (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected from interviews with students at SMK Pawyatan Daha 1, Kediri City. The development of learning resources by design was carried out using an educational application, IslamiQuest (IQ), which can display several features in a simple, creative, innovative, clear, and up-to-date manner. This development was made to make it easier for teachers to deliver materials and for students to find information, work on problems, and improve their understanding of the material. The study found that using the IslamiQuest application can attract students' interest in learning and improve their understanding and learning outcomes, as the learning resources presented in the application align with students' interests and current developments. Therefore, the development of learning resources by design, using online platforms such as the IslamiQuest application, plays an important role in improving learning quality by tailoring designs to students' needs and enabling them to better understand the learning material. Keywords: Learning Resources, Islamic Education, IslamiQuest, Technology